Model predictive control for tendon‐driven balloon actuator on simulation. (17th June 2016) - Nagase, Jun‐ya; Hamada, Kazuki; Satoh, Toshiyuki; Saga, Norihiko
Abstract : Many pneumatic actuators have been developed to be lightweight with high output for decreasing the impact force. However, for pneumatic actuators it is difficult to maintain exact control because these actuators have constraints. In this study, we developed model predictive control (MPC) that can accommodate these constraints when applied to the pneumatic actuator we developed. As described here, we compared and evaluated the control performance using MPC and proportional–integral–derivative (PID) control with an anti‐windup control system. © 2016 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.